Microsurgical Debridement for Persistent Ulcers Due to Rare Fungus Infection: Case Report and Literature Review - Tsui, Yu-Wen; Tsai, Chia-Yu; Chen, Hung-Chi (Archives of Plastic Surgery, 2024)
A patient suffered from chronic ulcer due to recalcitrant fungal infection for 3.5 years. Five antifungal agents and 40 times of debridement—all failed. Finally, radical microscopic debridement was performed for eradication of fungal conidiospores. Since then, there was no recurrence at 2 years of follow-up. Scopulariopsis brevicaulis is one of the rarest pathogens of cutaneous fungal infections, for which multidrug resistance increased the complexity and difficulty of treatment. Radical excision, especially microscopic debridement, was the key for eradication of fungal conidiospores in this case.
Keywords: fungal infections; wounds and injuries; Scopulariopsis brevicaulis; antifungal agents; microsurgical debridement